2020
DOI: 10.1063/5.0007547
|View full text |Cite
|
Sign up to set email alerts
|

Polaritonic normal modes in transition state theory

Abstract: A series of experiments demonstrate that strong light-matter coupling between vibrational excitations in isotropic solutions of molecules and resonant infrared optical microcavity modes leads to modified thermally-activated kinetics. However, Feist and coworkers [Phys. Rev. X., 9, 021057(2019)] have recently demonstrated that, within transition state theory, effects of strong light-matter coupling with reactive modes are electrostatic, and essentially independent of light-matter resonance or even of the format… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
147
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(150 citation statements)
references
References 40 publications
2
147
1
Order By: Relevance
“…7,8,29,31,32 On the other hand, since there is no theoretical explanation of the mechanism yet, it is not understood whether this is true. 20,[22][23][24] However, the phenomenological evidence for it relies on the correct identification of vibrational modes in the experimental IR spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,29,31,32 On the other hand, since there is no theoretical explanation of the mechanism yet, it is not understood whether this is true. 20,[22][23][24] However, the phenomenological evidence for it relies on the correct identification of vibrational modes in the experimental IR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…22 In contrast, in VSC experiments with Fabry-Pérot cavities, rates of S N 2@Si reactions are only found to be modified when polaritons are formed, in particular, when a cavity mode is in resonance with a molecular vibration involved in the reaction coordinate. 7,8 For the purposes of this work, we would like to highlight that at the present time, there is no clear physical explanation as to how vibrational strong coupling can slow down or accelerate thermal reactions in solution taking place inside Fabry-Pérot cavities, 20,[22][23][24] and that further theoretical work in this direction is highly desirable to rationalize the experimental observations. This being said, considering (i) the intricacies of S N 2 reactions that will be discussed in the following lines, and (ii) that vibrational strong coupling experiments have reported modified rates of S N 2@Si reactions, we believe that prior to deciphering how the reaction path is modified in the complex strong-coupling situation, the reaction mechanism under normal conditions should be fully understood.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, a number of theoretical studies have been developed since the first observation of the VSC‐modified reaction kinetics. Many theoretical works continue to appear which do not predict appreciable reactivity change in experimentally relevant scenarios . Much work lies ahead before routine prediction of VSC‐modulated chemistry is possible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent developments have found that vibrational strong coupling (VSC) can resonantly enhance thermally-activated chemical reactions via the formation of vibrational polaritons. 35,36 Currently, the majority of microscopic models for strong coupling in polaritonic chemistry employ few-level model systems. Some studies further add nuclear degrees of freedom using effective damping rates, 37,38 or by explicitly including vibrational modes 39 to examine their influence on the polariton properties.…”
Section: Introductionmentioning
confidence: 99%